PENGARUH BEBAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT BANK CENTRAL ASIA TBK KCU KELAPA GADING - Marcella Putri; Tarwijo (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Abstract - The purpose of this study was to determine the Effect of Workload and Work Discipline on Employee Performance of PT Bank Central Asia Tbk KCU Kelapa Gading both partially and simultaneously. The method used is quantitative. The sampling technique used saturated sampling and obtained a sample of 80 respondents. Data analysis used validity test, reliability test, classical assumption test, regression analysis, correlation coefficient, determination coefficient and hypothesis test with the help of SPSS software version 27. The results of this study are workload has a significant effect on employee performance with a determination coefficient value of 59.7% and the hypothesis test obtained t count> t table or (9.278> 2.002). Work discipline has a significant effect on employee performance with a determination coefficient value of 65.9% and the hypothesis test obtained t count> t table or (10.584> 2.002). Workload and work discipline simultaneously have a significant effect on employee performance with a regression equation = 8.891 + 0.163X1 + 0.624X2. The coefficient of determination is 66.4%, while the remaining 33.6% is influenced by other factors. The hypothesis test obtained a calculated F value > F table or (56.311 > 2.770).